Simulation of Tidal Inundation along the Northern Coast of Central Java (Pantura) Using GIS-Based Analysis - Robbani, Hilma; Kartikasari, Adelia Nur Isna; Pranantya, Vanadani; Kaffa, Niswah Selmi (GEOID, 2025)
The northern coast of Java Island (locally known as Pantura), is a strategically important area, particularly in the distribution sector. However, its topographical characteristics and proximity to the Java Sea make it vulnerable to the threat of tidal inundation. Moreover, environmental factors such as sea level rise, land subsidence, and coastal abrasion—which causes shoreline retreat—further exacerbate the region’s susceptibility to flooding. The rob phenomenon significantly impacts the socio-economic conditions of coastal communities, disrupting daily activities and damaging critical infrastructure such as residential housing and road networks. This study aims to simulate the impact of tidal flooding in terms of inundation depth and spatial extent, using the assumption of the Highest High Water Level (HHWL). The simulation results are intended to serve as an initial reference for the development of coastal flood mitigation strategies. The methodology follows the Technical Guidelines for Disaster Risk Assessment issued by Indonesia’s National Disaster Management Agency (BNPB) and integrates various spatial datasets, including land cover data from Sentinel Land Cover by ESRI, topographic data from the Shuttle Radar Topography Mission (SRTM) Digital Elevation Model (DEM), and maximum tidal height data processed using the Admiralty method. The analysis shows that, assuming a Highest High Water Level of 1.2 meters, Kendal Regency, Brebes Regency, and Semarang City are the most affected areas in terms of both flood depth and extent. The inundated areas are estimated at 3,744.91 hectares in Kendal Regency, 2,880.58 hectares in Brebes Regency, and 513.17 hectares in Semarang City. This situation could become more severe in the event of storm surge, extreme weather, or climate anomalies if timely and effective mitigation measures are not implemented. These findings are expected to provide a strong foundation for policymakers to formulate targeted, data-driven, and sustainable mitigation strategies to protect communities and infrastructure along Java’s northern coastal region.